Contrastive analysis and translation study from a corpus linguistics perspective - Gómez Castejón, María Ángeles (International Journal of English Studies, 2012)
Previous contrastive studies between the English gerund and its Spanish counterparts present serious limitations in the analysis of these constructions. The main objection is the absence of a cognitive approach. In addition, the traditional characterization of the English gerund seems to be inappropriate to determine its nature. We propose that in order to carry out a contrastive analysis of these constructions, it is absolutely necessary to include a cognitive approach. This approach establishes a valid characterization of the English gerund as well as the relationship between this category and its Spanish counterparts. We also include a translation study. The translation study is not limited to the establishment of equivalence relations between the source and target languages, but it also provides translations techniques observed in the translation product. On the whole, parallel corpora and translated texts prove to be extremely useful for both our contrastive analysis and translation study.